100km-scale isotopic (d18O, dD) variability of the top-meter between B31 and Kohnen, Dronning Maud Land (M samples) - Melanie Behrens; Maria Hörhold; Remi Dallmayr; Thomas Laepple; Johannes Freitag; Frank Wilhelms (PANGAEA, 2025)
Isotopic composition of the top-meter of the snowpack along a 115km traverse between B31 and D50, near Kohnen station, Dronning-Maud Land, East-Antarctica. Site D2 refers to the firn core drilling site B31. At each sampling site, profiles were sampled at 10 m distance in 90 m long trenches: _R samples using the dual-tube sampling technique (Dallmayr et al., 2020), 3 subsections of the top-1m were sampled and at sites C4, C5, D2, D7, D24, D38, the top-1m of the trenches were sampled with the dual-tube and 5 single liners were taken and subsampled to 1 - 3 cm resolution (Hirsch, Nora; Hörhold, Maria; Dallmayr, Remi; Laepple, Thomas; Freitag, Johannes; Meyer, Hanno; Weiner, Mikaela (2023): Stable water isotopologues of arrays of high resolution 1 m snow cores from across Dronning Maud Land, East Antarctic Plateau [dataset]. PANGAEA, https://doi.org/10.1594/PANGAEA.956273) _M samples: Mixed 4 subsections of the top-1.2m of the 90m long trenches excavated by Pistenbully. All isotopic analysis were realized by CRDS (Cavity-Ring-Down Spectroscopy) measurements at the Alfred-Wegener-Institut Helmholtz-Zentrum für Polar-und Meeresforschung in Bremerhaven (instrument models L-2120-i, L-2140-i, Picarro Inc.). The samples were shipped frozen to the Alfred-Wegener-Institut and stored at -25°C. Prior to measurements the samples were melted in the sample bags at room temperature. The measurement set-up followed the Van-Geldern Protocol. Each sample was injected four times and the standard deviation is computed.